2015
DOI: 10.1177/0886260514567966
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Mental Health Consequences of Sexual Violence Among Women Living With HIV in Rural Uganda

Abstract: The association between sexual violence and depression is well known, but the temporal aspects of the association have not been well established. We analyzed data from a cohort of 173 HIV-positive women in rural Uganda who were interviewed every 3 months for a median of 1.8 years of follow-up. The method of generalized estimating equations (GEE) was used to model the marginal expectation of depression symptom severity (Hopkins Symptom Checklist for Depression), mental health–related quality of life (MOS-HIV Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 108 publications
(125 reference statements)
0
39
2
Order By: Relevance
“…Average scores were generated for depression (15 item) and anxiety (10 item) subscales; higher scores indicating greater severity. To estimate a cutoff for clinically relevant symptoms, we averaged all 25 items into a single score; an average HSCL-25 score of 1.75 or higher was considered clinically significant (Kinyanda, Hoskins, Nakku, Nawaz, & Patel, 2011; Tsai et al, 2015). Internal consistency (Cronbach’s alpha) was 0.73, and 0.84 for the depression and anxiety subscales, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Average scores were generated for depression (15 item) and anxiety (10 item) subscales; higher scores indicating greater severity. To estimate a cutoff for clinically relevant symptoms, we averaged all 25 items into a single score; an average HSCL-25 score of 1.75 or higher was considered clinically significant (Kinyanda, Hoskins, Nakku, Nawaz, & Patel, 2011; Tsai et al, 2015). Internal consistency (Cronbach’s alpha) was 0.73, and 0.84 for the depression and anxiety subscales, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Trained research assistants conversant in the local language (Runyankole) administered the surveys through face-to-face interviews in private rooms of the ISS clinic. In August 2007, the survey was modified for a sub-study to include measures on relationship power, intimate partner violence, stigma, social support, health behaviors, and food security [45]. We performed a cross-sectional analysis using baseline data on all female participants from the sub-study (i.e., women who were enrolled into the cohort after the relationship power and other measures were introduced).…”
Section: Methodsmentioning
confidence: 99%
“…Although the association of victimization and depression is well elucidated, the temporal aspect of this association has not been well established. Study results indicated that victimization predicted greater depression symptom severity and lower mental health-related quality of life as well as heavy drinking [31]. Although substance abuse has been consistently associated with trauma and IPV [2, 21], this study was one of the few recent studies identified to explore this relationship.…”
Section: Trauma and Mental Healthmentioning
confidence: 96%
“…IPV and other forms of gender violence have been consistently related to psychiatric symptoms among PLWH [10, 31]. Recent literature provides additional evidence of this relationship.…”
Section: Trauma and Mental Healthmentioning
confidence: 99%